Side‐by‐side comparability of batch and continuous downstream for the production of monoclonal antibodies. Issue 4 (29th January 2020) - David, Laura; Schwan, Peter; Lobedann, Martin; Borchert, Sven‐Oliver; Budde, Bastian; Temming, Maike; Kuerschner, Mike; Alberti Aguilo, Francisca Maria; Baumarth, Kerstin; Thüte, Tobias; Maiser, Benjamin; Blank, Andreas; et al.
Abstract: Continuous processing is the future production method for monoclonal antibodies (mAbs). A fully continuous, fully automated downstream process based on disposable equipment was developed and implemented inside the MoBiDiK pilot plant. However, a study evaluating the comparability between batch and continuous processing based on product quality attributes was not conducted before. The work presented fills this gap comparing both process modes experimentally by purifying the same harvest material (side‐by‐side comparability). Samples were drawn at different time points and positions in the process for batch and continuous mode. Product quality attributes, product‐related impurities, as well as process‐related impurities were determined. The resulting polished material was processed to drug substance and further evaluated regarding storage stability and degradation behavior. The in‐process control data from the continuous process showed the high degree of accuracy in providing relevant process parameters such as pH, conductivity, and protein concentration during the entire process duration. Minor differences between batch and continuous samples are expected as different processing conditions are unavoidable due to the different nature of batch and continuous processing. All tests revealed no significant differences in the intermediates and comparability in the drug substance between the samples of both process modes. The stability study of the final product also showed no differences in the stability profile during storage and forced degradation. Finally, online data analysis is presented as a powerful tool for online‐monitoring of chromatography columns during continuous processing. Abstract : The aim of this study was to evaluate whether batch and continuous downstream processing lead to comparable results regarding product quality attributes when performing a side‐by‐side comparability study. To the knowledge of the authors, it was demonstrated for the first time that changing the process mode does not impact final drug substance characteristics. This opens a way to switch the process mode—independent from the product life cycle, from clinical trials to large‐scale production.